Urgensi Zoologi Sastra Alquran: Studi Kasus Pada Seni Kisah Zoomorfik Al-Farasy Surat Al-Qari’ah - Muhamad Agus Mushodiq; Ibnu Burdah; Suja'i Suja'i; Mispani Mispani; Habib Shulton Asnawi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The Urgency of Qur’anic Literary Zoology: A Case Study on the Art of the Zoomorphic Story of Al-Farasy in Surah Al-Qari'ahThe criminalization of animals can be manifested in concrete actions and disproportionate interpretation of religious texts. This paper aims to describe the urgency of a literary zoological perspective on animal studies in the Quran and provide examples of its application in analyzing one of the cases of animal criminalization al-Farasy in Surat Al-Qari'ah. The author uses qualitative research methods with descriptive-interpretive analysis. The author uses the theory of Tasybih and Roland Barthes’s Semiotics theory with a literary zoological approach. The results of this paper are: First, literary zoology is essential for animal research in the Quran for several reasons. They are (1) animals in the Quran are included in the literary category, so that an important literary approach is presented to find the meaning behind the existential of animals in the Quran, (2) ) Literary zoology is interdisciplinary, multidisciplinary, and transdisciplinary. Based on these characteristics, the zoosembiology between literature and animals can be expressed comprehensively and holistically, (3) literary zoological opposes anthropocentric philosophy, which is alleged to have produced many actions that destroy nature. Nature conservation, especially related to the future of animals, needs to be encouraged in the current era. Second, the discrimination against al-Farasy by the ulama resulted in monodisciplinary studies. Al-Farsy as an example of humans when the Day of Judgment comes is not meant for taqbih halihi (humiliating the human condition when the Day of Judgment comes), but rather for bayanu halihi and taqriru halihi (reporting the situation)